Genome-Wide Identification, Expression Profiling, and Evolution of Phosphate Transporter Gene Family in Green Algae - Wang, Long; Xiao, Liang; Yang, Haiyan; Chen, Guanglei; Zeng, Houqing; Zhao, Hongyu; Zhu, Yiyong (Frontiers in Genetics, 2020)
Phosphorus (P) is an essential nutrient for plant growth and development. Phosphate transporters (PHTs) are trans-membrane proteins that mediate the uptake and translocation of phosphate (Pi) in green plants. The PHT family including PHT1, PHT2, PHT3 and PHT4 subfamilies are well-studied in land plants; however, PHT genes in green algae are poorly documented and not comprehensively identified. Here, we analyzed the PHTs in a model green alga Chlamydomonas reinhardtii and found 25 putative PHT genes, which can be divided into four subfamilies. The subfamilies of CrPTA, CrPTB, CrPHT3, and CrPHT4 contain four, eleven, one, and nine genes, respectively. The structure, chromosomal distribution, subcellular localization, duplication, phylogenies, and motifs of these genes were systematically analyzed in silico. Expression profile analysis showed that CrPHT genes displayed differential expression patterns under P starvation condition. The expression levels of CrPTA1 and CrPTA3 were down-regulated, while the expression of most CrPTB genes was up-regulated under P starvation, which may be controlled by CrPSR1. The transcript abundance of most CrPHT3 and CrPHT4 genes was not significantly affected by P starvation except CrPHT4-3, CrPHT4-4, and CrPHT4-6. Our results provided basic information for understanding the evolution and features of the PHT family in green algae.